A review: achievements and new obstacles in China's food security revealed by grain and animal meat production. Issue 1 (March 2021) - Yang, Chaowu; Jiang, Xiaosong; Du, Huarui; Li, Qingyun; Zhang, Zengrong; Qiu, Mohan; Yu, Chunlin
Abstract: Food security represents that everyone is able to purchase and afford enough food necessary for survival and health at any time, which closely connects with harmonious society, stable policies and sustainable economic growth and plays a significant role in heavily populated countries such as China. Currently, while providing 1.4 billion people with adequate food, China has greatly enhanced people's nutrition and living quality. However, as economy develops, Chinese people are no longer satisfied with fulling up. In this research, China's achievements in food security are reviewed, including yields of grain and meat, food consumption and poverty elimination. Additionally, the strategies to safeguard food security in China are identified, including safeguarding the quantity and quality of arable land, farmers' interests, meat production and food reserves. Finally, major obstacles in China's food security revealed by grain and meat production in the new era are analyzed. Meanwhile, it is argued that the food security will not disappear as a permanent topic because food is enough temporarily; therefore, some implementation suggestions are put forward based on current situation and trend of food security.